Meningkatkan Kreativitas Peserta Didik Melalui Model Pembelajaran Berbasis Proyek (Project Based Learning) di SMP Negeri 22 Kota Jambi : (Increasing Student Creativity Through Project Based Learning Models at SMP Negeri 22 Kota Jambi) - Zaharah Zaharah; Mangudor Silitonga (BIODIK, 2023)
Facing demands to carry out out HOTS learning, teachers find it difficult, develop a  creative mindset . Moreover, dealing with students who feel bored during class learning, are lazy to  work on questions given by the teacher, lack of understanding of students about the material  provided by the teacher, students often chat during learning, donot dare to express opinions, are  not enthusiastic about learning. The right learning model makes students play an active role in the learning process, so  that it can encourage and increase learning motivation and increase student creativity. One of the  science learning models is Project Based Learning (PjBL). the PjBL model is learning steps to  achieve certain learning objectives that are carried out throug a project within a certain period of  time. The purpose of writing this research to describe the author’s reseach in  implementing learning using a project based learning model (Project Based Learning / PjBL). The  research location was carried out at SMP Negeri 22 Jambi city. The number of subjects was 28  people concisting of 16 women and 12 men. The learning process is carried out by applying the PjBL learning model to make students  active, improve students’ ability to transfer knowledge, think critically and solve problems (problem  solving) as well as increase student creativity and achievement. Of the two people who took part in  the poster design competition, both of the got achievements, the 3rd place was the male and the  most favorite was female. The recommendations given by the teacher should not only teach with  reference to student books and teacher books but must have the courage to make contextual  learning innovations according to the background of students and the situation and conditions of  their school. Gifted students must be given further guidance to develop their talents. Schools,  especially principals, can encourrage other teachers to participate in implementing HOTS- oriented  learning through the problem- based learning (PjBL) model. Abstrak. Menghadapi tuntutan untuk melaksanakan pembelajaran HOTS guru merasa  kesulitan terutama untuk mengembangkan sikap kreatif. Apalagi menghadapi peserta  didik yang merasa bosan pada saat pembelajaran dikelas, malas mengerjakan soal yang  diberikan guru, kurangnya pemahaman peserta didik tentang materi yang diberikan guru, Peserta didik sering mengobrol saat pembelajaran, tidak berani mengungkapkan pendapat  Tidak bersemangat dalam belajar. Model pembelajaran yang tepat membuat peserta didik lebih berperan aktif dalam  proses pembelajaran, sehingga dapat mendorong dan meningkatkan motivasi belajar serta  meningkatkan kreatifitas Peserta didik. Salah satu model pembelajaran sains adalah  Pembelajaran Berbasis Proyek/Project Based Learning (PjBL). Model PjBL adalah  langkah-langkah pembelajaran untuk mencapai tujuan pembelajaran tertentu yang  dilakukan melalui suatu proyek dalam jangka waktu tertentu Tujuan penulisan penelitian ini adalah untuk mendeskripsikan praktik terbaik  penulis dalam menerapkan pembelajaran dengan menggunakan model pembelajaran  berbasis proyek (Project Based Learning / PjBL). Lokasi penelitian dilaksanakan di SMP  Negeri 22 kota Jambi. Jumlah subjek sebanyak 28 orang yang terdiri dari 16 orang  perempuan dan 12 orang laki-laki. Proses pembelajaran yang dilakukan dengan menerapkan model pembelajaran  PjBL menjadikan peserta didik aktif, meningkatkan kemampuan peserta didik dalam  melakukan transfer knowledge, berpikir kritis dan memecahkan masalah (problem solving)  serta meningkatkan kreatifitas dan prestasi peserta didik. Rekomendasi yang diberikan  guru seharusnya tidak hanya mengajar dengan mengacu pada buku siswa dan buku guru  tetapi harus berani melakukan inovasi pembelajaran yang kontekstual sesuai dengan  latar belakang peserta didik dan situasi dan kondisi sekolahnya, Peserta didik berbakat  harus diberikan bimbingan lebih lanjut untuk mengembangkan bakatnya. Sekolah,  terutama kepala sekolah dapat mendorong guru lain untuk ikut melaksanakan  pembelajaran berorientasi HOTS melalui model pembelajaran problem based learning (PjBL).